2013
DOI: 10.7150/ijms.6749
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α -857C>T Genotype is Predictive of Clinical Response after Treatment with Definitive 5-Fluorouracil/cisplatin-based Chemoradiotherapy in Japanese Patients with Esophageal Squamous Cell Carcinoma

Abstract: Background: Genotypes of tumor necrosis factor alpha (TNF-α) and its surface receptors, TNFRSF1A and TNFRSF1B, have been examined in terms of the progression, metastasis, clinical efficacy, and prognosis of various cancers; however, little is known about their effects on clinical outcome in patients with esophageal squamous cell carcinoma (ESCC). In this study, TNF-α and TNFRSF1A genotypes were retrospectively evaluated in terms of predicting clinical response, long-term survival, and severe acute toxicities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…No association was found between TNFR1 rs2234649 and gastric mucosa-associated lymphoid tissue lymphoma [24], and in myelopathy associated to HTLV-1 infection [37]. However, controversial results were found in TNFR1 rs767455 SNPs, where no association was described in esophageal squamous cell carcinoma [23], while a significant increased risk for breast cancer [38, 39] and odontogenic keratocystic tumor [40] were observed. Moreover, others TNFR1 SNPs have been described in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No association was found between TNFR1 rs2234649 and gastric mucosa-associated lymphoid tissue lymphoma [24], and in myelopathy associated to HTLV-1 infection [37]. However, controversial results were found in TNFR1 rs767455 SNPs, where no association was described in esophageal squamous cell carcinoma [23], while a significant increased risk for breast cancer [38, 39] and odontogenic keratocystic tumor [40] were observed. Moreover, others TNFR1 SNPs have been described in different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…This receptor is the main mediator of TNF signaling pathways, affecting the binding of TNF-α in the membrane [17]. A growing number of genetic studies have identified several single nucleotide polymorphisms (SNPs) in the TNFR1A gene as susceptibility or predictive markers of multifactorial inflammatory disorders [18–22] and cancer [2328]. One of the functional consequences of these variants could be linked to regulation of gene expression [29].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor alpha was known as a cytokine that could kill cancer cells; however, sometimes it can cause the reproduction, invasion, and metastasis of cancer cells (25). Therefore, elevated TNF-α levels may have deleterious outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α activates signals for pathways starting within two receptors: tumor necrosis factor receptor superfamily member 1A (TNFRSF1A (CD120a) and TNFRSF1B (CD120b) [ 12 , 13 , 14 ]. It plays a critical role in non-lysosomal and lysosomal proteolytic pathways, induction of the ubiquitin-proteasome pathway, decrease in protein synthesis, decrease in adipose tissue enzymes (e.g., lipoprotein-lipase), and simultaneous increase in adipose tissue lipolysis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%